2006
DOI: 10.1002/clc.20
|View full text |Cite
|
Sign up to set email alerts
|

Control of rapid heart rate changes for electrocardiographic analysis: implications for thorough QT studies

Abstract: SummaryBackground: Following an abrupt change in heart rate (HR), QT adaptation is achieved within a delayed time frame.Hypothesis: The exclusion of electrocardiograms (ECGs) showing rapid HR changes influences the level of a drug-induced QT prolongation.Methods: Continuous 12-lead ECG-Holter monitoring was performed in 31 healthy subjects. Using the "bin" method, we evaluated moxifloxacin effects on (1) QT interval duration at different RR intervals and (2) on the rate dependence of QT interval. These endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In agreement with our data, Yuan et al reported that the effect of dofetilide on in situ human monophasic APD90 is not rate-dependent (Yuan, Wohlfart, Rasmussen, Olsson, & Blomstrom-Lundqvist, 1994). In contrast, other studies reported that drug-induced prolongation of ventricular repolarization with dofetilide, sotalol and moxifloxacin was more pronounced with slow pacing rates (Extramiana et al, 2006; Funck-Brentano et al, 1991; Lande et al, 1988; Okada, Ogawa, Sadanaga, & Mitamura, 1996). Therefore, drug action as a function of pacing rate in the human heart warrants further assessment.…”
Section: Discussionmentioning
confidence: 88%
“…In agreement with our data, Yuan et al reported that the effect of dofetilide on in situ human monophasic APD90 is not rate-dependent (Yuan, Wohlfart, Rasmussen, Olsson, & Blomstrom-Lundqvist, 1994). In contrast, other studies reported that drug-induced prolongation of ventricular repolarization with dofetilide, sotalol and moxifloxacin was more pronounced with slow pacing rates (Extramiana et al, 2006; Funck-Brentano et al, 1991; Lande et al, 1988; Okada, Ogawa, Sadanaga, & Mitamura, 1996). Therefore, drug action as a function of pacing rate in the human heart warrants further assessment.…”
Section: Discussionmentioning
confidence: 88%
“…The power of such investigations will be substantially increased (and thus the necessary study size decreased) if the combined individual-specific corrections for both heart rate and hysteresis are used. Correcting QT interval individually for both rate and hysteresis appears clearly preferable to preselecting ECG data in which the effect of QT/RR hysteresis is considered unimportant because of heart rate stability (8).…”
Section: Discussionmentioning
confidence: 99%
“…27 Figure 4 shows that, when applying our stability filter, the percentage of rejected beats was correlated with the HR variability parameter PNN50. For instance, a noise filter can be set to reject noisy QRS-T complexes and the minimal number of QRS-T complexes defining a template may also be selected to improve the signal-to-noise ratio.…”
Section: Qt Durationmentioning
confidence: 96%